Achievement of children in an alternative education programme for refugee, stateless and undocumented children in Sabah, Malaysia - Vincent Pang; Mei-Teng Ling; Rose Patsy Tibok (Penerbit UNISZA, 2019)
Access to formal education is an arduous and difficult process for undocumented and stateless children with entry into government schools often hindered by their status and prevailing national policies and procedures. The Alternative Education Programme (AEP) is structured as a response for the need to provide some form of schooling for children under this classification. This study investigated students’ attainment in the AEP curriculum at Murni Alternative Education Centre (MAEC). A questionnaire, which incorporated a proxy pre-test, measured the achievement of children pre and post-participation in the MAEC learning among 136 female and 113 male learners with the mean age being 10.17 years. Achievement of the intended outcomes of the MAEC curriculum was investigated using Rasch Analysis. Achievement of MAEC objectives was demonstrated in the five curriculum components. In Literacy and Numeracy, item difficulty of reading, speaking, writing and counting showed significant decreases. In Religious Practice, a slight improvement was found with learners able to read the Quran and perform Islamic obligations and acts of worship. For Civics and Citizenship, increase in awareness and appreciation of Malaysian nationhood was ascertained with almost all children identifying themselves as ‘Malaysians’. Improvement in Self-Management was also demonstrated through increased awareness of personal hygiene and well-being except in the matter of environment upkeep. For Living Skills, the majority concurred that MAEC learning equipped them with skills to generate income. These insights into the MAEC learning outcomes from the perspectives of learners themselves could serve as guidelines towards any restructuring of AEP curriculum in MAEC in particular, and Sabah in general.